Cognitive and behavioral modernity in Homo erectus: skull globularity and hominin brain evolution - Clark Gary; Henneberg Maciej (Anthropological Review, 2022)
In this article we provide evidence that evolutionary pressures altered the cranial base and the mastoid region of the temporal bone more than the calvaria in the transition from H. erectus to H. sapiens. This process seems to have resulted in the evolution of more globular skull shape – but not as a result of expansion of the brain in the parietal regions but of reduction of the cranial base and the mastoid region relative to the parietals. Consequently, we argue that expansion of the parietals seems to be unrelated to brain evolution, but is more a by-product of reduction in other regions of the skull, reduction that may be related to dietary factors. Additionally, these findings suggest that cognitive and behavioural modernity may not necessarily be dependent on brain shape. Also, it cannot be attributed to the change in brain size because H. erectus and modern human cranial capacities overlap substantially. Consequently, we suggest H. erectus possessed the full suite of cognitive adaptations characteristic of modern humans without possessing a globular skull with flared parietals. Our results also support the theory that paedomorphic morphogenesis of the skull was important in the transition from H. erectus to H. sapiens and that such changes may be related to both dietary factors and social evolution.